Assessing Outsourced Workers' Normative Rights Protection in the Electricity Sector Following Labor Policy Reform - Gede, I Gede Ayusta DG; Marwati Riza (Media Iuris, 2026)
Protection for workers aims to ensure welfare, equality of rights, and freedom from discrimination, including for outsourced workers as implemented by PLN. The enactment of the Job Creation Law has brought changes to the outsourcing contract scheme at PLN, which was previously based solely on subcontracting and has now changed to three types: subcontracting, volume-based, and mixed. The change in the contract scheme has affected the status of outsourced workers, making them workers with Fixed-Term Employment Agreements (PKWT) who are no longer directly recorded and supervised by PLN. This condition triggers the potential vulnerability of normative rights for outsourced workers, such as job security, severance pay, social security, and protection from termination of employment. This research emphasizes the need for policy evaluation and adjustment to ensure that the legal protection for outsourced workers continues to align with the constitution and principles of social justice. This study aims to analyze the impact of Law Number 11 of 2020 concerning Job Creation (Job Creation Law) on the legal protection and rights of outsourced workers at PT PLN (Persero) Makassar Region, highlighting the shift in contract schemes from permanent to fixed-term contracts and the potential weakening of protections, as well as providing policy recommendations for social justice and legal certainty for workers. The research uses a doctrinal method with systematic and qualitative analysis of the relationships between regulations, concluding with an analysis of PLN's outsourcing policy post-Job Creation Law, which includes guarantees when outsourcing workers' rights.